EVALUASI PROGRAM KONSELING DI SMP KOTA MALANG: DISCREPANCY MODEL - Wahyu Nanda Eka Saputra (Program Studi bimbingan Konseling PPs UNM Makassar, 2015)
This study aims to determine the discrepancy between the performance of counseling program of Junior High School in Malang with the determined standards. This study uses a standard of Guidelines for Performance Based Professional School Counselor Evaluation. In the standard it was found that, “the professional school counselor counsels individual students and small groups of students with identified needs/concerns”. This study is an evaluation research. Evaluations were performed in this study using a discrepancy model. The approach used is a system approach that is focused on the planning, implementation, and evaluation of counseling programs. Based on the analysis of the results of the evaluation, counseling programs in Junior Hight School in Malang is still far from standard. The results of this study recommend to counselors to improve the quality of the counseling program, so that it will give a positive impact on students.